Expert opinion on the prescription practice of topical calamine lotion for chronic urticaria and other dermatologic conditions in Indian clinical settings - S., Manjula; Kumar M., Krishna (International Journal of Research in Dermatology, 2024)
Background: Calamine is suggested as a potentially effective treatment for skin exudation, itching, and rashes. However, there aren’t many thorough analyses of the drug prescription patterns for treating urticaria in the Indian literature. This study aimed to gather expert opinions on the prescription practice of topical calamine lotion for chronic urticaria and other dermatologic conditions in Indian clinical settings. Methods: The cross-sectional questionnaire-based survey, comprising 25 questions, gathered data regarding the prescription practice of topical calamine lotion for the management of chronic urticaria and other dermatological conditions. Results: Of the 467 participants, 62% indicated that they would prescribe topical calamine lotion for pruritus management. About 39% of the participants preferred the cream formulation of the calamine lotion for treating diaper dermatitis in 11-25% of patients. About 76% of the respondents stated that they would recommend an oral antihistamine along with topical calamine lotion to treat chronic urticaria. For the treatment of pruritus, 44% of the participants preferred menthol in addition to calamine. Sixty-eight per cent of the respondents stated that approximately 5% of those with chronic urticaria need to be treated with calamine and tetrahydrocurcumin. Most specialists (69.38%) preferred using calamine lotion on 5-10% of patients with itchy skin conditions during pregnancy. Conclusions: Experts recommend the topical calamine lotion for managing various skin conditions including pruritus and chronic urticaria. Specialists recommended it as a safe option for managing itchy skin conditions during pregnancy.